Similarities and differences between lightning and electrical injuries: two case reports - Yi Liu; Zosimo Ken L. Jimeno; Wan Azman Wan Sulaiman (Journal of Trauma and Injury, 2025)
Exposure to electrical current, whether through accidental contact in residential or industrial settings or via lightning strikes, represents a serious global health concern. Although numerous studies have been published on the differences between electrical and lightning injuries, they are often discussed together due to the similarities in their clinical presentations, management approaches, and outcomes. The question of whether electrical and lightning injuries should be studied together remains a matter of debate. Here, we present two cases: one of a lightning injury and another of an electrical injury. Our discussion aims to improve the understanding of lightning and electrical injuries as distinct entities. Vigorous resuscitative measures are recommended and given the complexity of electrical and lightning injuries and their long-term sequelae, patients should be managed in a multidisciplinary burn center. Furthermore, the knowledge and awareness of the general population must be improved to reduce the incidence of such injuries.